Doc Hollywood [videorecording (DVD)] - Price, Jeffrey; Seaman, Peter S.; Pyne, Daniel, 1955-; Fox, Michael J., 1961-; Warner, Julie, 1965-; Hughes, Barnard, 1915-2006; Harrelson, Woody; Fonda, Bridget; Shulman, Neil (Archive collection., 2016)
A big-city doctor on the way to a job interview in L.A. gets stranded in a small town in forced to do community service in the way of medical work. Although eager to leave, a local beauty might persuade him to stay.